2018
DOI: 10.1002/jcop.22124
|View full text |Cite
|
Sign up to set email alerts
|

Sense of place attitudes and quality of life outcomes among African residents in a multicultural Australian society

Abstract: The study examines the association between sense of place (SOP) attitudes (e.g., place attachment, place identity, and place dependence) and health-related quality of life (HQOL) in a sample of 261 African residents in New South Wales (Australia). Participants completed measures of the Sense of Place Scale, the World Health Organization Quality of Life-BREF questionnaire, and demographic variables. Study findings are as follows: (a) levels of SOP and place attachment are positively associated with all outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 73 publications
(126 reference statements)
2
14
0
Order By: Relevance
“…The findings of the present research are in line with the results of the research of Gheitarani et al (2020). It also supports and confirms the results of Counted (2019) about the relationship between Sense of place attitudes on the quality of life of a specific community. The results of the research also confirmed the findings of Mousazadeh (2021), in relation to the impact of the river and strengthening the quality of life and the sense of place of the citizens who live by the river.…”
Section: Sense Of Placesupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the present research are in line with the results of the research of Gheitarani et al (2020). It also supports and confirms the results of Counted (2019) about the relationship between Sense of place attitudes on the quality of life of a specific community. The results of the research also confirmed the findings of Mousazadeh (2021), in relation to the impact of the river and strengthening the quality of life and the sense of place of the citizens who live by the river.…”
Section: Sense Of Placesupporting
confidence: 91%
“…Table 2 show the outcomes of univariate and multivariate analyses that were measured to examine the main effects of sense of place attitudes on quality of life outcomes, and all sociodemographic variables with a pvalue < .10 were entered in the adjusted model examining the relationship between sense of place attitudes and quality of life outcomes. For each outcome, two models are proffered: (a) the unadjusted model (Model 1) and (b) the adjusted model (Model 2) (Counted, 2019). Significance was set at p < 0.05.…”
Section: Sense Of Placementioning
confidence: 99%
See 1 more Smart Citation
“…Adedeji et al [ 23 ] found that subjective integration was positively associated with the physical and psychological health of sub-Saharan African migrants in Germany. Victor’s [ 24 ] results showed that place identity as an aspect of self-identity was positively related to HRQOL of African migrants in Australia. A study among migrants in Shanghai illustrated that subjectivity was an important factor in reducing migrants’ psychological pressure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, a developing amount of research has shown that SOP attitudes are correlated with QOL outcomes (e.g., [28][29][30][31][32]), environmental and natural factors such as urban rivers and parks (e.g., [5,[33][34][35][36]), inhabitants in rural and metropolitan areas (e.g., [37][38][39][40][41][42]), and wellness and psychological research (e.g., [29,[43][44][45][46]).…”
Section: Introductionmentioning
confidence: 99%